Evaluation of Flexible and Integrative Psychiatric Treatment Models in Germany—A Mixed-Method Patient and Staff-Oriented Exploratory Study - von Peter, Sebastian; Ignatyev, Yuriy; Johne, Jakob; Indefrey, Sonja; Kankaya, Onur Alp; Rehr, Burkhard; Zeipert, Manfred; Bechdolf, Andreas; Birkner, Thomas; Deister, Arno; Duve, Annette; Rout, Sandeep; et al. (Frontiers in Psychiatry, 2019)
Contrary to the practice in some countries, access to flexible and integrated forms of psychiatric care (FIT models) is limited in Germany. Several legislations have been introduced to improve this situation, notably the recent §64b (flexible and integrative treatment model; FIT64b) of the German Social Code, which allows for a capitation-based accounting of fees for services. The aim of this study was to explore the effects of FIT64b implementation on various stakeholders (patients, informal caregivers and staff) in 12 psychiatry departments across Germany. Structural as well as quantitative and qualitative data were included, with integration of different methodological approaches. In all departments, the implementation of the new accounting system resulted into a relatively stable set of structural and processual changes: Rigid forms of mainly inpatient care shifted to more flexible and integrated types of outpatient and outreach treatments. These changes were more likely to be perceived, and received better evaluations, by both patients and staff in those departments showing higher level or longer duration of implementation. Patients’ evaluations, furthermore, were largely influenced by the advent of continuous forms of care, better accessibility, and by their degree of autonomy in steering of services.